From Escherichia coli heat-stable enterotoxin to mammalian endogenous guanylin hormones - Lima, A.A.M. (Associação Brasileira de Divulgação Científica, 2014)
The isolation of heat-stable enterotoxin (STa) from Escherichia coli and cholera toxin from Vibrio cholerae has increased our knowledge of specific mechanisms of action that could be used as pharmacological tools to understand the guanylyl cyclase-C and the adenylyl cyclase enzymatic systems. These discoveries have also been instrumental in increasing our understanding of the basic mechanisms that control the electrolyte and water balance in the gut, kidney, and urinary tracts under normal conditions and in disease. Herein, we review the evolution of genes of the guanylin family and STa genes from bacteria to fish and mammals. We also describe new developments and perspectives regarding these novel bacterial compounds and peptide hormones that act in electrolyte and water balance. The available data point toward new therapeutic perspectives for pathological features such as functional gastrointestinal disorders associated with constipation, colorectal cancer, cystic fibrosis, asthma, hypertension, gastrointestinal barrier function damage associated with enteropathy, enteric infection, malnutrition, satiety, food preferences, obesity, metabolic syndrome, and effects on behavior and brain disorders such as attention deficit, hyperactivity disorder, and schizophrenia.